AN ANALYSIS OF DEIXIS IN ‘DOLITTLE’ MOVIE - Ayu Yusfika; Anwar Ismail; Silvani Umar Ali (Universitas Khairun, 2022)
Deixis is a word that shows the emphasis of a sentence on an object addressed by the speaker. This study also relates the grammatical elements in it where there are five types of deixis, each of which to has a word that indicates the sentence spoken by the speaker is shown to whom. This study investigated the five types of deixis in the film 'Dolittle' and found all the deixis in the film. In this film, it was found 1,238-person deixis (70.14%), 226 discourse deixis (12.76%), 150 social deixis (8.47%), 106 place deixis (5.98%), 45-time deixis (2.54%).